2023
DOI: 10.1038/s41746-023-00876-x
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness review of text messaging, smartphone application, and website interventions targeting T2DM or hypertension

Ruben Willems,
Lieven Annemans,
George Siopis
et al.

Abstract: Digital health interventions have been shown to be clinically-effective for type 2 diabetes mellitus (T2DM) and hypertension prevention and treatment. This study synthesizes and compares the cost-effectiveness of text-messaging, smartphone application, and websites by searching CINAHL, Cochrane Central, Embase, Medline and PsycInfo for full economic or cost-minimisation studies of digital health interventions in adults with or at risk of T2DM and/or hypertension. Costs and health effects are synthesised narrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…However, there are specific telemedicine cost analysis studies that may provide assistance with cost considerations. In a recently published study on the cost-effectiveness of telemedicine interventions, smartphone app, SMS text messaging, and website interventions were confirmed to be cost-effective without substantial differences among the different delivery modes [ 70 ]. A study by Elliott et al [ 71 ] showed that smart wearable devices increase short-term costs but their HbA 1c -lowering benefits will provide sufficient long-term health benefits and cost savings to justify the costs as long as the effects last into the medium term.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are specific telemedicine cost analysis studies that may provide assistance with cost considerations. In a recently published study on the cost-effectiveness of telemedicine interventions, smartphone app, SMS text messaging, and website interventions were confirmed to be cost-effective without substantial differences among the different delivery modes [ 70 ]. A study by Elliott et al [ 71 ] showed that smart wearable devices increase short-term costs but their HbA 1c -lowering benefits will provide sufficient long-term health benefits and cost savings to justify the costs as long as the effects last into the medium term.…”
Section: Discussionmentioning
confidence: 99%
“…The need for more evidence regarding multimodal digital health interventions and their mechanisms of impact has been highlighted by others [57][58][59][60]. Recent work assessing the (cost) effectiveness of digital interventions of different modalities to support type 2 diabetes self-management have demonstrated that while cost-effectiveness might be similar across some of the common modalities [61], text message and app-based interventions may be more effective overall and have greater reach than web-based interventions [62]. Future work should seek to address these questions for interventions targeting prediabetic populations.…”
Section: Plos Onementioning
confidence: 99%